2021
DOI: 10.1016/j.jcmgh.2021.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Intestinal Barrier Function by Microbial Metabolites

Abstract: The human gastrointestinal tract (GI) harbors a diverse population of microbial life that continually shapes host pathophysiological responses. Despite readily available abundant metagenomic data, the functional dynamics of gut microbiota remain to be explored in various health and disease conditions. Microbiota generate a variety of metabolites from dietary products that influence host health and pathophysiological functions. Since gut microbial metabolites are produced in close proximity to gut epithelium, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
251
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(256 citation statements)
references
References 203 publications
1
251
0
4
Order By: Relevance
“…In any case, the changes in the SCFA production observed during IDW fecal fermentation were associated with the modulation of the microbiome by the digested-wine fluid. SCFA, mainly acetic, propionic, and butyric acids, are attracting considerable interest because of their possible importance for health and for the protection of the intestinal barrier integrity [ 41 ]. With regard to IP, a pioneering study by Mariadason et al [ 42 ] first reported the capacity of SCFAs to reduce paracellular permeability in Caco-2 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, the changes in the SCFA production observed during IDW fecal fermentation were associated with the modulation of the microbiome by the digested-wine fluid. SCFA, mainly acetic, propionic, and butyric acids, are attracting considerable interest because of their possible importance for health and for the protection of the intestinal barrier integrity [ 41 ]. With regard to IP, a pioneering study by Mariadason et al [ 42 ] first reported the capacity of SCFAs to reduce paracellular permeability in Caco-2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Many other later studies have investigated the mechanisms surrounding this effect [ 43 , 44 , 45 ]. Regarding butyric and acetic acids, two well-known SCFAs derived from carbohydrate fermentation related to a protective effect on the intestinal barrier function by up-regulating tight junction protein claudin-1 or facilitating tight junction assembly [ 41 , 45 ], results revealed lower levels in the presence of IDW. It could be due to the decrease detected in the proportions of Lachnospira , Ruminococcus , and Bacteroides genus members, some of the main producers of these SCFA on gut microbiota [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…SCFAs, as metabolites of the gut bacteria, are used by epithelial cells as their primary energy source to promote the health of the GI system [91]. SCFAs improves the expression of connexin in intestinal epithelial cells by enhancing the expression of the MUC2 gene and activating the AMP-activated protein kinase (AMPK) pathway [92]. Moreover, SCFA has an impact on the population and function of innate immune cells through G-protein coupled receptor signaling and HDAC inhibition and plays an important role in maintaining the intestinal barrier function [91,93].…”
Section: Bifidobacterium Longum Enhances the Intestinal Barriermentioning
confidence: 99%
“…It forms a semipermeable barrier that allows the absorption of essential nutrients, electrolytes, and water from the intestinal lumen into the circulation, and conversely curbs harmful insults arising from the external environment or the commensal microbiota [28]. In turn, the gut microbiota contributes to maintaining epithelial barrier physiology through the production of several metabolites such as short-chain fatty acids (SCFAs), indoles, and polyphenol metabolites that maintain epithelial cell turnover and barrier integrity by regulating tight junction (TJ) gene expression [29]. In addition, SCFAs represent a main energy source for colonocytes and exert a variety of anti-inflammatory properties, influencing mucosal immune cell migration, cytolytic activity, cytokine production, and the secretion of antimicrobial peptides by intestinal epithelial cells and macrophages [30,31].…”
Section: The Intestinal Epithelial Barriermentioning
confidence: 99%